2004
DOI: 10.1021/cm021783l
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium Aluminum Garnet Nanopowders Produced by Liquid-Feed Flame Spray Pyrolysis (LF-FSP) of Metalloorganic Precursors

Abstract: We report here the synthesis of yttrium-aluminum garnet oxide (Y 3 Al 5 O 12 ) nanopowders by liquid-feed flame spray pyrolysis (LF-FSP) of combinations of yttrium and aluminum precursors dissolved in EtOH, n BuOH, and/or THF. These include solutions of the following: yttrium and aluminum nitrates in EtOH or n BuOH; yttrium 2-ethylhexanoate and alumatrane [N(CH 2 CH 2 O) 3 Al] in THF or EtOH; yttrium methoxyacetate and alumatrane in EtOH; yttrium acetylacetonate and alumatrane in EtOH, and yttrium propionate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 40 publications
4
83
0
Order By: Relevance
“…The resulting nanopowder was found to form a new hexagonal Y 3 Al 5 O 12 phase, which we describe here. In studies reported in detail elsewhere, [13] we found that 3:5 mixtures of Y(O 2 CCH 2 CH 3 ) 2 OH and Al(Acac) 3 (Acac = acetylacetonate) dissolved in ethanol gave nanopowders with average particle sizes (APS) below 50 nm (Fig. 1a).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The resulting nanopowder was found to form a new hexagonal Y 3 Al 5 O 12 phase, which we describe here. In studies reported in detail elsewhere, [13] we found that 3:5 mixtures of Y(O 2 CCH 2 CH 3 ) 2 OH and Al(Acac) 3 (Acac = acetylacetonate) dissolved in ethanol gave nanopowders with average particle sizes (APS) below 50 nm (Fig. 1a).…”
supporting
confidence: 54%
“…(LF-FSP). [13] In this process, metallo-organic precursors (e.g., metal carboxylates) with the exact composition of the metals desired in the final oxide nanopowders are dissolved in an alcohol (typically ethanol) and the solutions aerosolized with oxygen. The aerosol mist is ignited to produce flame temperatures exceeding 1500 C. Rapid quenching of the gas-phase species produces nanosized oxide ªsootº with the exact metal composition of the starting solution, including any impurities or dopants.…”
mentioning
confidence: 99%
“…Amongst others, nanoparticles of ceria, yttrium stabilized zirconia (YSZ), ceria-zirconia (CeZrO 4 ) or other mixed-oxides (Backman et al, 2004;Marchal et al, 2004;Makela et al, 2004) in general are produced next to optical components or polishing additives (Madler et al, 2002b). Milling has been suggested as a possible route to nanoparticles and has successfully be implemented in YSZ production (Michel et al, 1993).…”
Section: Mixed Oxide Nanoparticlesmentioning
confidence: 99%
“…Formerly, the main limitation was due to the availability of volatile precursors to be fed to the flame. More recently, aerosol or liquid-feed flame pyrolysis (FP) allowed to overcome the low productivity problem, hence widely extending the application field of flame synthesis [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Among the methods proposed, the spray FP seems the most interesting for the production of perovskitic oxides, since it does not require volatile precursors.…”
Section: -Introductionmentioning
confidence: 99%